Shubnikov–de Haas measurements on a high mobility monolayer graphene flake sandwiched between boron nitride sheets. (28th April 2017) - Matsumoto, Naoki; Mineharu, Masaaki; Matsunaga, Masahiro; Chuang, Chiashain; Ochiai, Yuichi; Oto, Kenichi; Kim, Gil-Ho; Watanabe, Kenji; Taniguchi, Takashi; Ferry, David K; da Cunha, Carlo R; Aoki, Nobuyuki
Abstract: A flake of monolayer graphene was sandwiched between boron nitride sheets. Temperature dependent Shubnikov–de Haas measurements were performed to access how this technique influences the electronic properties of the graphene sample. The maximum mobility found in this configuration was approximately 10 5 cm 2 Vs −1 . From the phase of the oscillations a Berry phase β of 1/2 was obtained indicating the presence of Dirac fermions. We obtained Fermi velocities around 0.8 × 10 6 m s −1 which imply hopping energies close to 2.5 eV. Furthermore, the carrier lifetime is typically higher than that found in graphene supported by SiO2, reaching values higher than 700 fs.